1998
DOI: 10.1063/1.120573
|View full text |Cite
|
Sign up to set email alerts
|

Optical modes within III-nitride multiple quantum well microdisk cavities

Abstract: Optical resonance modes have been observed in optically pumped microdisk cavities fabricated from 50 Å/50 Å GaN/Al x Ga 1Ϫx N(xϳ0.07) and 45 Å/45 Å In x Ga 1Ϫx N/GaN(xϳ0.15) multiple quantum well structures. Microdisks, approximately 9 m in diameter and regularly spaced every 50 m, were formed by an ion beam etch process. Individual disks were pumped at 300 and 10 K with 290 nm laser pulses focused to a spot size much smaller than the disk diameter. Optical modes corresponding to ͑i͒ the radial mode type with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 9 publications
0
32
0
1
Order By: Relevance
“…[4][5][6] Enhanced quantum efficiency ͑QE͒ and optical resonant modes have been observed in these microcavities. Most recently, we have fabricated electrically pumped InGaN/GaN QW individual -disk LEDs with a diameter of about 10 m and it was shown that the QE was higher in -disk LEDs than in the conventional broad-area LEDs.…”
mentioning
confidence: 98%
“…[4][5][6] Enhanced quantum efficiency ͑QE͒ and optical resonant modes have been observed in these microcavities. Most recently, we have fabricated electrically pumped InGaN/GaN QW individual -disk LEDs with a diameter of about 10 m and it was shown that the QE was higher in -disk LEDs than in the conventional broad-area LEDs.…”
mentioning
confidence: 98%
“…These modes were observed at an excitation power density of 4.82 kW/cm 2 , which is over 5 times lower than the power densities previously reported for a GaN-based microdisks [4,5]. However, the microdisks exhibit a large background of optical noise.…”
Section: Resultsmentioning
confidence: 47%
“…However, to date, the most notable GaN-based microdisk results have been from structures which use the lower refractive index of the sapphire substrate for vertical optical confinement and a single dry etch step to form disks for lateral optical confinement. These devices have shown rather broad, low Q emission and required high pump power densities (25 kW/cm 2 average power from a picosecond excitation source) [4,5]. Using bandgap selective photoelectrochemical (PEC) etching [6,7], we have fabricated mushroom-shaped GaN disks with InGaN active regions which exhibit high Q values from 1700-2700.…”
Section: Introductionmentioning
confidence: 99%
“…Nitride-based lasers operating at λ ≈ 0.4µm [19][20][21] have much higher M -values (200 < ∼ M < ∼ 600) and n ≈ 2.8. This yields FWHM of 64…”
Section: Discussionmentioning
confidence: 99%